2002
DOI: 10.1007/s11738-002-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-induced changes in lipid peroxidation, superoxide level and antioxidant enzymes activity in neem (Azadirachta indica A. Juss) seeds

Abstract: The freshly harvested mature neem seeds (42.2 % seed moisture content) with 100 % viability deteriorate when naturally desiccated to below 10.9 %. The desiccation-induced loss of viability was closely associated with over accumulation of superoxide anion and lipid peroxidation products both in the embryonic axes and cotyledons. The levels of superoxide anion and lipid peroxidation products were higher in axes compared to cotyledons. Superoxide dismutase activity was not much affected, both in the axes and coty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…Thus, the desiccation of G. biloba seeds accompanied by a deepening degree of membrane lipid oxidation led to the severe damage of the membrane system, causing a large accumulation of MDA. This was consistent with seeds of Azadirachta indica [50] and Pachira macrocarpa [51]. However, it is important to mention that a decline from 30% to 25% MC was observed in Figure 7, where with respect to SOD and POD, the peak values were found at 25% and 30% MC, respectively ( Figures 5 and 6), and the germination percentage kept constant.…”
Section: Changes Of Mda Content In G Biloba Seeds During Desiccationsupporting
confidence: 85%
“…Thus, the desiccation of G. biloba seeds accompanied by a deepening degree of membrane lipid oxidation led to the severe damage of the membrane system, causing a large accumulation of MDA. This was consistent with seeds of Azadirachta indica [50] and Pachira macrocarpa [51]. However, it is important to mention that a decline from 30% to 25% MC was observed in Figure 7, where with respect to SOD and POD, the peak values were found at 25% and 30% MC, respectively ( Figures 5 and 6), and the germination percentage kept constant.…”
Section: Changes Of Mda Content In G Biloba Seeds During Desiccationsupporting
confidence: 85%
“…In the third week of June, mature ripe yellow fruits of Azadirachta indica A. Juss (neem) 12 weeks after flowering (Varghese and Naithani, 2002) were harvested manually from trees growing in Pt. Ravishankar Shukla University campus, Raipur, and brought to the laboratory immediately.…”
Section: Seed Collection and Extractionmentioning
confidence: 99%
“…A few seeds from the lot were immediately depulped mechanically to determine the seed water content, which is hereafter referred to as the initial water content. Seeds were extracted from the fruit tissue by soaking them in 20% H 2 SO 4 (Merck, India) for 30 min after depulping by rubbing with hands over a wire mesh and washing repeatedly under tap water as described elsewhere (Varghese and Naithani, 2002).…”
Section: Seed Collection and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also been reported to display orthodox behaviour (Roederer and Bellefontaine, 1989;Bellefontaine and Audinet, 1993;Tompsett and Kemp, 1996;Sacandé et al, 2000b). Other studies concluded that neem seeds belong to the intermediate category of storage behaviour (Gaméné et al, 1996;Sacandé et al, 1996;Hong and Ellis, 1998;Varghese and Naithani, 2002). Many factors, such as seed provenance, maturity at harvest and conditions of storage and sensitivity to imbibition, have been suggested to explain these apparent controversies.…”
Section: Introductionmentioning
confidence: 98%